Reconstruction of Intra-Oral Defects with Submental Artery Flap: A Comparison of pN+ and pN0 Oral Squamous Cell Carcinoma Patients - Abdullah Khan, Riaz Ahmed Warraich, Sadiq Ali, Ashfaq-Ur-Rahim, Muhammad Nauman, Urooj Kirmani, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To compare the reconstruction of intra-oral defects with submental artery flap among pN+ and pN0 oral squamous cell carcinoma patients. Methodology: A comparative analytical prospective study was conducted in the Department of Oral and Maxillofacial Surgery, University of Lahore, from January 1, 2022, to November 1, 2022. Fifty-five confirmed cases of oral squamous cell carcinoma were included. The inclusion criteria were based on oral cavity carcinoma patients presenting for tumour resection and reconstruction of the resultant defects with the submental artery flap. A pinch test was applied to estimate the flap width, wherein the flap length and skin paddle were designed in accordance with the defect size. Results: The mean age of the patients was 58.81±1.2 years, with a significant variance in the pN+ and pN0 patients below 60 years of age. There were 27 males and 18 females with primary treatment of T1–4 OSCC. The primary site of the tumour was observed to be highest in the tongue region in pN+ (52.17%) and pN0 (43.75%) cases, followed by the buccal mucosa, which presented with 30.43% of pN+ cases and 37.5% in pN0 patients. The majority of the patients had moderately differentiated tumours in pN+ (82.6%) and pN0 (56.25%) patients. Within the 55 cases for reconstruction with SAFs, there were 58.1% who had pN0, while 41.8% had pN+ presentation. In the pN0 patients, 96.8% did not have any recurrence, while only 1 patient had local or regional recurrence in the neck region. Conclusion: Vigilant neck dissection, in addition to suitable adjuvant treatments, does not increase the loco-regional recurrence risk in patients suffering from pN+ oral squamous cell carcinoma. Keywords: Lymph nodes, submental artery flap (SAF), reconstruction, oral squamous cell carcinoma (OSCC)